PENGARUH BIAYA PROMOSI DAN BIAYA DISTRIBUSI TERHADAP PENJUALAN PADA PT. UNILEVER INDONESIA, Tbk. - Maduretno Widowati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2011)
To increase sales volume, PT Unilever Indonesia focused on marketing strategy especially marketing mix strategy, including promotion and distribution. How many products have been sold depend on promotion and distribution cost allocated by corporate. This research analized the effect of promotion and distribution cost to increase sales volume’s PT Unilever Indonesia. The result proved that promotion and distribution cost have a significant effect on sales volume.